The feasibility of an automated eye-tracking-modified Fagan test of memory for human faces in younger Ugandan HIV-exposed children. Issue 5 (4th July 2018) - Chhaya, Ronak; Weiss, Jonathan; Seffren, Victoria; Sikorskii, Alla; Winke, Paula M.; Ojuka, Julius C.; Boivin, Michael J.
ABSTRACT: Objective : The Fagan Test of Infant Intelligence (FTII) uses longer gaze length for unfamiliar versus familiar human faces to gauge visual-spatial encoding, attention, and working memory in infants. Our objective was to establish the feasibility of automated eye tracking with the FTII in HIV-exposed Ugandan infants. Method : The FTII was administered to 31 perinatally HIV-exposed noninfected (HEU) Ugandan children 6–12 months of age (11 boys; M  = 0.69 years, SD  = 0.14; 19 girls; M  = 0.79, SD  = 0.15). A series of 10 different faces were presented (familiar face exposure for 25 s followed by a gaze preference trial of 15 s with both the familiar and unfamiliar faces). Tobii X2-30 infrared camera for pupil detection provided automated eye-tracking measures of gaze location and length during presentation of Ugandan faces selected to correspond to the gender, age (adult, child), face expression, and orientation of the original FTII. Eye-tracking gaze length for unfamiliar faces was correlated with performance on the Mullen Scales of Early Learning (MSEL). Results : Infants gazed longer at the novel picture compared to familiar across 10 novelty preference trials. Better MSEL cognitive development was correlated with proportionately longer time spent looking at the novel faces ( r (30) = 0.52, p  = .004); especially for the Fine Motor Cognitive Sub-scale ( r (30) = 0.54, p  = .002). Conclusion : Automated eye tracking in a human face recognition test proved feasible and corresponded to the MSEL composite cognitive development in HEU infants in a resource-constrained clinical setting. Eye tracking may be a viable means of enhancing the validity and accuracy of other neurodevelopmental measures in at-risk children in sub-Saharan Africa.